A Socio-Psychological approach to understanding Child Rape: An analytical study - Lemoueldi, Awatef Atil (Journal of Humanities & Social Sciences, 2021)
This paper is about children rape crime; which represents one of the sexual violence patterns. This later has serious psychological, social and health effects on the child and grow up with him. Thus, it is regarded as the most dangerous kind of crimes against the child. This crime has come out of social and psychological factors. So, we studied this topic through the sociological theory and the psychological theory.
Keywords: crime; rape; sexual violence; child